2020
DOI: 10.3866/pku.whxb202009071
|View full text |Cite
|
Sign up to set email alerts
|

Developing Practical Lithium-Air Batteries by Avoiding Negative Effects of CO<sub>2</sub>

Abstract: The gradual popularization of new energy technologies has led to rapid development in the field of electric transportation. At present, the demand for high-power density batteries is increasing and next-generation higherenergy battery chemistries aimed at replacing current lithiumion batteries are emerging. The lithium-air batteries (LABs) are thought to be the ultimate energy conversion and storage system, because of their highest theoretical specific energy compared with other known battery systems. Current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 77 publications
(95 reference statements)
0
5
0
Order By: Relevance
“…7 However, lithium-air batteries are more like lithium-oxygen batteries because they have to work in a pure oxygen environment rather than in ambient air. 8,9 In 2011, Takechi and co-workers 10 found that adding a moderate amount of CO 2 to the Li-O 2 battery atmosphere (pure O 2 ) could greatly increase the discharge capacity of the battery (up to almost 3 times), leading to the creation of the original Li-O 2 /CO 2 battery. Following this line of thinking, the first Li-CO 2 battery that worked in a pure CO 2 atmosphere was developed in 2013, which, in the next several years, rapidly became a promising strategy for CO 2 fixation and utilization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 However, lithium-air batteries are more like lithium-oxygen batteries because they have to work in a pure oxygen environment rather than in ambient air. 8,9 In 2011, Takechi and co-workers 10 found that adding a moderate amount of CO 2 to the Li-O 2 battery atmosphere (pure O 2 ) could greatly increase the discharge capacity of the battery (up to almost 3 times), leading to the creation of the original Li-O 2 /CO 2 battery. Following this line of thinking, the first Li-CO 2 battery that worked in a pure CO 2 atmosphere was developed in 2013, which, in the next several years, rapidly became a promising strategy for CO 2 fixation and utilization.…”
Section: Introductionmentioning
confidence: 99%
“…To solve this problem, lithium–air batteries with ultrahigh energy density have been developed 7 . However, lithium–air batteries are more like lithium–oxygen batteries because they have to work in a pure oxygen environment rather than in ambient air 8,9 . In 2011, Takechi and co‐workers 10 found that adding a moderate amount of CO 2 to the Li–O 2 battery atmosphere (pure O 2 ) could greatly increase the discharge capacity of the battery (up to almost 3 times), leading to the creation of the original Li–O 2 /CO 2 battery.…”
Section: Introductionmentioning
confidence: 99%
“…23 Therefore, to achieve a high utilization ratio of Al–air batteries, the self-corrosion of Al metal and polarization should be suppressed simultaneously. 24…”
mentioning
confidence: 99%
“…CO 2 could participate in the discharge reactions, reacting with the superoxide intermediate and peroxide final product to form Li 2 CO 3 . However, Li 2 CO 3 hardly shows any XRD peaks due to its poor crystallinity.…”
mentioning
confidence: 99%
“…CO 2 could participate in the discharge reactions, reacting with the superoxide intermediate and peroxide final product to form Li 2 CO 3 . 25 However, Li 2 CO 3 hardly shows any XRD peaks due to its poor crystallinity. Therefore, we quantify the Li 2 CO 3 in the electrodes by using DEMS as described in the Experimental Section.…”
mentioning
confidence: 99%